2001
DOI: 10.1212/wnl.57.11.2108
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids reduce levodopa-induced dyskinesia in Parkinson’s disease: A pilot study

Abstract: The lateral segment of the globus pallidus (GPl) is thought to be overactive in levodopa-induced dyskinesia in PD. Stimulation of cannabinoid receptors in the GPl reduces gamma-aminobutyric acid (GABA) reuptake and enhances GABA transmission and may thus alleviate dyskinesia. In a randomized, double-blind, placebo-controlled, crossover trial (n = 7), the authors demonstrate that the cannabinoid receptor agonist nabilone significantly reduces levodopa-induced dyskinesia in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
203
1
12

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(218 citation statements)
references
References 6 publications
2
203
1
12
Order By: Relevance
“…A small but class III randomized double-blind study using nabilone (synthetic Δ 9 -THC) showed a significant reduction in Rush score on levodopa-induced dyskinesias in 7 patients, observed and measured with the Rush dyskinesia scale [16], and 2 reported improvement in dystonia occurring in the off period for dopa. In a study of 17 patients using the oral preparation Cannador (2.5 mg Δ 9 -THC/1.25 mg CBD) no improvement was noted in dyskinesias as measured in Q32-34 of the Unified Parkinson's disease rating scale scale (the primary outcome), or other scales including Parkinson Disease Questionnaire-39 scale, nor was there a dose response [17].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…A small but class III randomized double-blind study using nabilone (synthetic Δ 9 -THC) showed a significant reduction in Rush score on levodopa-induced dyskinesias in 7 patients, observed and measured with the Rush dyskinesia scale [16], and 2 reported improvement in dystonia occurring in the off period for dopa. In a study of 17 patients using the oral preparation Cannador (2.5 mg Δ 9 -THC/1.25 mg CBD) no improvement was noted in dyskinesias as measured in Q32-34 of the Unified Parkinson's disease rating scale scale (the primary outcome), or other scales including Parkinson Disease Questionnaire-39 scale, nor was there a dose response [17].…”
Section: Dyskinesias From Levodopa (In Advanced Pd)mentioning
confidence: 99%
“…This stimulation may also change the reuptake of GABA in striatal references. 21 It also reduces glutamate release in basal ganglia. 22 In PD, CB1 receptors are increased in basal ganglia and treatment with levodopa restores the levels to normal numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, only two small-scale clinical trials have shown that marijuana was ineffective in reducing Parkinsonian tremor, but recently a randomized, double blind, placebo-controlled, cross-over trial with the cannabinoid receptor agonist nabilone showed an improvement in L-DOPA-induced dyskinesia in patients with PD (Sieradzan et al, 2001). This obviously contrasts the animal studies that suggest that CB 1 receptor antagonists may be used to reduce the adverse actions of L-DOPA.…”
Section: Parkinson's Diseasementioning
confidence: 95%